Role of Locoregional Therapies in Patients With Hepatocellular Cancer Awaiting Liver Transplantation. (23rd January 2021) - Thuluvath, Paul J.; To, Chau; Amjad, Waseem
Abstract : Hepatocellular cancer (HCC) is the fifth most common cancer in the world and the third most common cause of cancer-related deaths. The United Network for Organ Sharing has its own staging criteria for organ allocation, which is a modification of tumor-node-metastasis staging of American Joint Committee on Cancer. For the purpose of clarity, United Network for Organ Sharing staging will be described as uT1, uT2 (Milan criteria), and uT3 (eligible for downstaging) in this review. For those with unresectable HCC or those with advanced liver disease and HCC but within the Milan criteria, liver transplantation is the treatment of choice. Because of prolonged waiting period on the liver transplant list in many parts of the world for deceased donor liver transplantation, there is a serious risk of dropout from the liver transplant list because of tumor progression. For those patients, locoregional therapies might need to be considered, and moreover, there is circumstantial evidence to suggest that tumor progression after locoregional therapies might be a surrogate marker of unfavorable tumor biology. There is no consensus on the role or type of locoregional therapies in the management of patients with uT1 and uT2 eligible for liver transplant and of those with lesions larger than uT2 but eligible for downstaging protocol (uT3 lesions). In this review, we examine the role of locoregional therapies in these patients stratified by staging and propose treatment options based on the current evidence of tumor progression rates while awaiting liver transplantation and tumor recurrence rates after liver transplantation.